The Influence of Leadership Style and Organizational Commitment on Employee Loyalty at Tomoro Coffee Bandar Lampung - Vincen Wiriya Lie; Hendri Dunan (Universitas Negeri Surabaya, 2026)
Employee loyalty has become a critical determinant of organizational sustainability, particularly in the service industry, where employee performance directly influences customer satisfaction and organizational competitiveness. Despite its importance, coffee retail businesses continue to experience high employee turnover, absenteeism, and inconsistent work discipline, indicating challenges in maintaining employee loyalty. Previous studies have reported inconsistent findings regarding the relative influence of leadership style and organizational commitment on employee loyalty, while empirical evidence from Indonesia's rapidly growing coffee retail sector remains limited. This study aims to examine the influence of leadership style and organizational commitment on employee loyalty among employees of Tomoro Coffee Bandar Lampung. A quantitative approach was employed using a saturation sampling technique involving 34 employees. Data were collected through structured questionnaires and analyzed using multiple linear regression. The findings reveal that leadership style has a positive but statistically insignificant effect on employee loyalty, whereas organizational commitment has a significant positive effect. Furthermore, both variables simultaneously influence employee loyalty, with organizational commitment emerging as the dominant predictor. This study contributes to the organizational behavior literature by providing empirical evidence from the Indonesian coffee retail industry, demonstrating that psychological attachment to the organization plays a more decisive role in fostering employee loyalty than leadership style alone. The findings also provide practical implications for managers by highlighting the importance of strengthening organizational commitment through supportive organizational policies, employee development, and recognition programs to improve employee retention and organizational performance.